Judging similarity versus judging difference - Humphry, Stephen; Montuoro, Paul (Frontiers in Education, 2023)
A key feature of the polytomous Rasch model is that it entails a single classification process into one of a set of ordered response categories. The first aim of this article is to make explicit two processes in rubric designs that bring about such classifications, and identify implications of the distinction between them. The first process involves judgements of similarity, typified by judgements that a performance is similar to a category description. The second process involves judgements of difference. It is typified by judgements that a performance is better than a category description. In this article, each process is explicated using a hypothetical context in which assessors compare performances with exemplars. The second aim is to demonstrate that, for reporting purposes, judgements of similarity are recommended, particularly when results are interpreted by persons with limited knowledge of the Rasch model and its parameters. In judgements of similarity, category descriptions are located at the peak of each category probability curve, at the point of highest probability in each the category, with thresholds located between them. This is clearer than judgements of difference, where category descriptions are located at the thresholds, and where the point of highest probability has no material reference. This is explicated using a simple real-world example. Implications for rubric design are discussed, as well as implications for related types of instruments, such as attitudinal measures and pairwise comparisons.